The Effect of Aceh Government Spending with Special Autonomy Fund Realization on Poverty Alleviation in Aceh Province - Mirza Fanzikri; Al-Ayubi, Fathurramahman (Sanger Journal: Social, Administration and Government Review, 2024)
The distribution of special autonomy funds by the Indonesian government to the Aceh government is expected to increase economic growth while reducing poverty in the province, which has long suffered from the conflict. By using multiple linear regression analysis, this paper aims to examine the extent to which Aceh's special autonomy funds (DOKA/Dana Otonomi Khusus Aceh) affect reducing the poverty rate. This paper provided the probabilistic prediction for poverty alleviation, which is explained by variables of DOKA, economic growth, and unemployment rate. After running the data by using R studio, the results show that DOKA and the Aceh government spending affect the poverty level in Aceh province. Also, economic growth affected the poverty level in the same period from 2008 to 2021. However, the unemployment rate as a variable control does not affect the poverty level in the several tests. In addition, this paper provided all predictor variables that can predict that every one-unit increase will affect the poverty level in Aceh province.